Quackbot Automated Robot Duck Egg Collector Based on Artificial Intelligence (AI) and Internet of Things (IoT) - Analiah Fahlevy Yusuf; Muhammad Arif Bagus Dewanto; Herlambang Nurasyid Ramadhan; Dhiya Rizqi Bagus Wibowo; Antonio Banggas Gregory Sinaga; Anandito Daffa Wijayanto; Afifah Rodhiyatun Nisa4; Lathifunnisa Fathonah; Gema Parasti Mindara; Mohamad Fikih Amar Dani (Batrisya Education, 2025)
The development of robotics in various fields is advancing rapidly, especially in the current digital era. In the world of egg retrieval, there are specific procedures to prevent eggs from breaking during collection. Many farms still rely on manual egg retrieval, where workers collect eggs daily. However, there are concerns about dishonest workers who may steal eggs for personal gain, causing worry for farmers. To address this issue, an AI-based egg picker has been designed to act as a system controller and information manager. This system includes AI for egg detection and an IoT system for real-time monitoring, allowing farmers to track daily egg yields. The development of this automatic egg-picking robot involves several stages: data collection, data analysis, block diagrams, planning, needs analysis, device design, implementation, and maintenance. The tool utilizes AI YOLOv8 to detect eggs, which the robot then collects. Once the maximum capacity is reached, the robot returns to the base camp. This innovative approach not only improves efficiency and accuracy in egg collection but also ensures transparency and reduces the risk of theft, providing peace of mind for farmers and enhancing overall farm productivity.